1991
DOI: 10.1093/geronj/46.4.b135
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dietary Restriction, Germ-Free Status, and Aging on Adrenal Catecholamines in Lobund-Wistar Rats

Abstract: Adrenal catecholamines (CA) were measured in 6-, 18-, and 30-mo Lobund-Wistar rats (LWR) maintained under germ-free or conventional conditions and fed either ad libitum or a restricted (70% of adult ad libitum) diet. Levels of dopamine (DA), norepinephrine (NE), epinephrine (E), and dihydroxymandelic acid (DHMA) were determined by HPLC-EC. Compared with values from 6- and 18-mo rats, mean adrenal weight, DA and NE content and concentration, and E content were increased in the 30-mo rats; E concentration was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Blood epinephrine levels do not change with CR in rats (50). Insulin may act by suppressing glucocorticoid stimulation of cpsI mRNA by 50% (15).…”
Section: Cpsi Levelsmentioning
confidence: 81%
“…Blood epinephrine levels do not change with CR in rats (50). Insulin may act by suppressing glucocorticoid stimulation of cpsI mRNA by 50% (15).…”
Section: Cpsi Levelsmentioning
confidence: 81%
“…In addition, norepinephrine has been reported to show a chemotactic effect, thereby increasing bacterial migration to the intestinal mucosa in the host [31].Norepinephrine concentration in blood is higher in germ-free mice than in conventional rodents [32]. Though the level of 5-HT did not change significantly between ND-fed and HFD-fed mice, the level of 5-HT in the hippocampus of HFD-induced mice was increased by TP treatment with a significant difference.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, recent studies have demonstrated that catecholamines also modulate host–microbial interface. Interestingly, in germ-free mice, serum norepinephrine is increased when compared with controls [ 45 ]. As described above, increased norepinephrine through the activity of tricyclic antidepressants is implicated in limiting glioma growth thus, our finding of decreased norepinephrine may help in driving glioma growth and progression.…”
Section: Discussionmentioning
confidence: 99%
“…These signaling molecules are able to interact with receptors of vagal afferents [52,53], as well as diffuse into circulation where they may act in an endocrine fashion [47,54]. Additionally, differences have been observed in serum norepinephrine levels between germ-free and controls in previous studies [45].…”
Section: Glioma Patients Controlsmentioning
confidence: 98%